2020
DOI: 10.1088/1361-648x/abc802
|View full text |Cite
|
Sign up to set email alerts
|

Molecular magnetism in the multi-configurational self-consistent field method

Abstract: We develop a structured theoretical framework used in our recent articles (2019 Eur. Phys. J. B 92 93 and 2020 Phys. Rev. B 101 094427) to characterize the unusual behavior of the magnetic spectrum, magnetization and magnetic susceptibility of the molecular magnet Ni4Mo12. The theoretical background is based on the molecular orbital theory in conjunction with the multi-configurational self-consistent field method and results in a post-Hartree–Fock scheme for constructing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…To study the experimentally observed magnetic properties of the compounds Na [Er(W O ) ] [ 9 ] and [(Pc)Er{Pc{N(C H ) } }] [ 24 ], we rely on the method proposed in Reference [ 25 ]. Here, we assume that a single molecule hosts no more than three unpaired valence electrons in its ground state with all non-bonding orbitals being fully occupied.…”
Section: The Hamiltonianmentioning
confidence: 99%
See 4 more Smart Citations
“…To study the experimentally observed magnetic properties of the compounds Na [Er(W O ) ] [ 9 ] and [(Pc)Er{Pc{N(C H ) } }] [ 24 ], we rely on the method proposed in Reference [ 25 ]. Here, we assume that a single molecule hosts no more than three unpaired valence electrons in its ground state with all non-bonding orbitals being fully occupied.…”
Section: The Hamiltonianmentioning
confidence: 99%
“…Under the considered assumptions and the introduced effective spin coupling scheme, the spin–sigma Hamiltonian reads (see e.g., Reference [ 25 ]) where is the intramolecular exchange parameter between the spin centers, the effective three components’ spin operator and the spin-like operator are associated to the i -th magnetic center. The operator in the field dependent term satisfies the relation where , with , is the -th component of the i -th spin operator and …”
Section: The Hamiltonianmentioning
confidence: 99%
See 3 more Smart Citations